2015
DOI: 10.14798/73.1.782
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF DIETARY SUPPLEMENTATION OF FUMARIC ACID ON GROWTH PERFORMANCE OF AFRICAN CATFISH Clarias gariepinus AND Aeromonas sobria CHALLENGE

Abstract: Five iso-nitrogenous (39.0% crude protein) and iso-caloric diets (510 kJ gross energy) were prepared with fumaric acid added at varying inclusion levels: 0 (D 1 ), 0.5 (D 2 ), 1.0 (D 3 ), 1.5 (D 4 ) or 2.0 (D 5 ) g kg -1 of diet. Diets were fed to triplicate groups of Clarias gariepinus (mean initial weight 68.14±1.5 g) for 84 days in 50 liters glass tanks. At the end of the experiment, fish fed diet D 3 gave significantly higher growth indices closely followed by the control diet (D 1 ). There were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Salts of organic acids used are calcium propionate, calcium formate and sodium acetate. Dietary fumaric acid (catfish) [41], fumaric and sorbic acid (E. coli) [42], citric acid (E. coli) [43], calcium propionate (tilapia [44] and silver catfish [45]), calcium formate (shrimp) [13] and sodium acetate (tilapia [46] and yellowfin seabream [47]) showed varying levels of antimicrobial activity in vitro and in various farmed species. Most studies to date tested a single compound in free-form and rarely a combination of two or more compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Salts of organic acids used are calcium propionate, calcium formate and sodium acetate. Dietary fumaric acid (catfish) [41], fumaric and sorbic acid (E. coli) [42], citric acid (E. coli) [43], calcium propionate (tilapia [44] and silver catfish [45]), calcium formate (shrimp) [13] and sodium acetate (tilapia [46] and yellowfin seabream [47]) showed varying levels of antimicrobial activity in vitro and in various farmed species. Most studies to date tested a single compound in free-form and rarely a combination of two or more compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The other benefits of butyric acid for improving growth is attributed to the aroma which acts as an attractant in the diet of shrimp 21 . However, a past study found that the increasing levels of dietary organic acid such as fumaric acid (1.5–2 g kg -1 ) in the diet of C. gariepinus significantly reduced growth performance and feed utilities and improved survival rate after a challenge test with bacteria 10 . These findings might be correlated with pH balance in the gut of the fish fed dietary high levels of organic acid.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, water quality parameters are a major concern in the aquaculture system. Previous research revealed that the values of water quality parameters during fumaric acid feeding experiments on the African catfish ( Clarias gariepinus ) are relatively stable, providing a dissolved oxygen concentration 7.23-7.86 mg L -1 , water temperature 25.13-25.27 0 C and pH 7.23-7.48 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Salts of organic acids used are calcium propionate, calcium formate, and sodium acetate. Dietary fumaric acid (catfish) [41], fumaric and sorbic acid (E. coli) [42], citric acid (E. coli) [43], calcium propionate (tilapia [44] and silver catfish [45]), calcium formate (shrimp) [13], and sodium acetate (tilapia [46] and yellowfin seabream [47]) showed varying level of antimicrobial activity in-vitro and in various farmed species. Most studies to-date tested a single compound in free-form and rarely, in combination of two or more compounds.…”
Section: Introductionmentioning
confidence: 99%